Optimizing Learning Environments: Strategic Planning, Organizing, and Storage Techniques Needed for Building Construction Workshops in Technical Colleges - Gana, D.; Mohammed, U.; Kumazhege, S. Z. (Darul Yasin Al Sys, 2024)
The main purpose of the study was to optimize the learning environments through strategic planning, organizing, and storage techniques needed by teachers for building construction workshops in technical colleges. The study was guided by three specific objectives, three research questions as well as three null hypotheses conducted in Gombe State using descriptive survey research design. The population for the study was 63 individuals, consisting of 21 School Administrators, 28 Building Construction Teachers, and 14 Workshop Staff from all Government Science and Technical Colleges in Gombe State. There was no sampling as the entire population was used because it was manageable. A structured questionnaire tagged titled